The Role of Dividend Policy in Mediating the Influence of Profitability, Leverage, And Liquidity on Company Value in Manufacturing Companies on the IDX - Edi Supriyono; Arkanuddin Latif (Lafadz Jaya Publisher, 2025)
This research aims to observe the role of Dividend Policy in mediating the influence of Profitability, Leverage and Liquidity on Company Value on the Indonesian Stock Exchange (BEI). This research is a type of quantitative research that tests causal relationships between variables. The data used is secondary data in the form of financial reports obtained from the official website of the Indonesia Stock Exchange and related companies using documentation methods. The objects studied are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. The samples used were taken using a purposive sampling method, totaling 297 observation samples from 107 companies. Data analysis was carried out using multiple linear regression and Sobel tests assisted by Eviews 12 software. Based on the findings from research that has been conducted, it shows that: (1) profitability has a significant positive effect on company value, (2) profitability has a significant positive effect on dividend policy, (3) leverage has a significant negative effect on company value, (4) leverage has no effect on dividend policy, (5) liquidity has no effect on company value, (6) liquidity has a significant positive effect on dividend policy, (7) dividend policy has a significant positive effect on company value, (8) dividend policy is able to mediate the effect of profitability on company value, (9) dividend policy is not able to mediate the effect of leverage on company value, (10) dividend policy is able to mediate the effect of liquidity on company value. The results of this research can be used as a reference by management in the decision-making process for the company, as well as considerations in making investment decisions by investors.